A pilot randomized controlled trial of transcranial direct current stimulation adjunct to moderate-intensity aerobic exercise in hypertensive individuals - Silva-Filho, Edson; Bikson, Marom; Gebodh, Nigel; Khadka, Niranjan; da Cruz Santos, Amilton; Pegado, Rodrigo; do Socorro Brasileiro-Santos, Maria (Frontiers in Neuroergonomics, 2024)
Background Hypertension is a global issue that is projected to worsen with increasingly obese populations. The central nervous system including the parts of the cortex plays a key role in hemodynamic stability and homeostatic control of blood pressure (BP), making them critical components in understanding and investigating the neural control of BP. This study investigated the effects of anodal transcranial direct current stimulation (tDCS) associated with aerobic physical exercise on BP and heart rate variability in hypertensive patients. Methods Twenty hypertensive patients were randomized into two groups: active tDCS associated with aerobic exercise or sham tDCS associated with aerobic exercise. BP and heart rate variability were analyzed before (baseline) and after twelve non-consecutive sessions. After each tDCS session (2 mA for 20 min), moderate-intensity aerobic exercise was carried out on a treadmill for 40 min. Results A total of 20 patients were enrolled (53.9 ± 10.6 years, 30.1 ± 3.7 Kg/m2). There were no significant interactions between time and groups on diastolic BP during wake, sleep, over 24 and 3 h after the last intervention. Heart rate variability variables showed no significant difference for time, groups and interaction analysis, except for HF (ms2) between groups (p < 0.05). Conclusion Anodal tDCS over the temporal cortex associated with aerobic exercise did not induce improvements in BP and heart rate variability. Clinical trial registration https://ensaiosclinicos.gov.br/rg/RBR-56jg3n/1, identifier: RBR-56jg3n.